Yayasan UMPSA Scholarship 2025: English Written Test at UMPSA - Fathiah Izzati, Mohammad Fadzillah (UMPSA, 2025)
PEKAN, 6 May 2025 – As part of the selection process for the Yayasan Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Scholarship 2025, 31 shortlisted candidates sat for the English Written Test today. The assessment, comprising Reading and Writing components, is a crucial step in evaluating applicants’ readiness for academic programmes conducted in English.